Validation of Sinhala Version of Cardiff Wound Impact Schedule in Patients with Diabetic Leg and Foot Ulcers - Kumarasinghe Arachchigey Sriyani, RN, BSc; Nalika Gunawardena, MD, MPH; Sudharshani Wasalathanthri, MBBS, PhD; Priyadarshika Hettiarachchi, PhD (Elsevier, 2016)
Purpose: To validate the Cardiff Wound Impact Schedule (CWIS) to assess the health-related quality of life (HRQoL) of Sri Lankan patients with diabetic leg and foot ulcers. Methods: English version of CWIS was examined for cultural compatibility, translated into Sinhala and pretested. The Sinhala version was administered in parallel with the validated Sinhala version of SF-36 by an interviewer to all patients (n = 140) at baseline to determine the construct validity. Reliability of CWIS was measured by internal consistency and test-retest stability. The instrument was readministered in 2 weeks on 33 patients with nonhealing ulcers to determine the test-retest stability and in 3 months on 50 patients with healed ulcers to determine the ability of CWIS to discriminate HRQoL between patients with healed versus nonhealed ulcers. Acceptability of CWIS was assessed by the response rate, completion rate and the average time taken to complete a single interview. Results: The construct validity demonstrated moderately significant correlations between related subscales of CWIS and SF-36 (Spearman's r = .32−.51, p = .021 to p < .001) for the whole study sample. Internal consistencies (Cronbach α = .68−.86) and test-retest stability (.56−.70) were acceptable. The tool was sensitive in discriminating the impact of the wound on HRQoL in healed versus nonhealed status (p ≤ .001). The tool showed good acceptability. Conclusions: The Sinhala version of CWIS is valid, reliable and acceptable for assessing the impact of wound on HRQoL. This instrument is sensitive in detecting the differences of the impact of healed and nonhealed ulcers on QoL in patients with diabetic leg and foot ulcer.